Hidden under darkened wings: the identity of Doryctobracon fluminensis (Lima, 1938) (Hymenoptera: Braconidae) and a new species of the genus from Brazil - Marinho, Cláudia F.; Shimbori, Eduardo M.; Alvarenga, Clarice D.; Zucchi, Roberto A. (Zootaxa, 2024)
Doryctobracon fluminensis (Lima) is one of several species of braconid parasitoids of fruit flies occurring in Brazil. Nearly 60 years passed after the original description by Lima (1938) until the publication of new records of D. fluminensis in several Brazilian states. Species identifications in these records were generally based on the darkened (infumate) fore wings, which has become the main character used in identification keys for recognizing D. fluminensis. After examination of the holotype of D. fluminensis, and comparison with several Brazilian specimens, we concluded that infumate fore wing alone is insufficient for separating species in the genus, as other Doryctobracon species also possess this feature. Here, we describe a new species, Doryctobracon simulatus Marinho sp. nov., based on specimens previously identified as D. fluminensis; redescribe D. fluminensis (Lima); and redefine the limits of D. maculatus Marinho. The misidentification discovered in the only two voucher specimens available indicates that other records of D. fluminensis in Brazil may also be incorrect, although those identifications cannot be verified. Our results demonstrate the importance of preserving voucher specimens in collections for future studies. An updated key to the species of Doryctobracon attacking fruit-infesting tephritids in Brazil is presented.